Musculoskeletal Injuries in Recreational Athletes as a Diagnostic Challenge in Acute Pain Syndromes – A Narrative Review - Ściążko-Gancarczyk, Sabina; Maliszewska, Małgorzata; Gancarczyk, Maciej; Węgrzyn, Jagoda; Marciniak, Kinga (Journal of Education, Health and Sport, 2026)
Background. Musculoskeletal injuries are a common consequence of recreational physical activity. In some cases, they may present as acute pain syndromes with a non-specific clinical presentation that can mimic symptoms of internal diseases. Objective. The aim of this study was to present the most common musculoskeletal injuries occurring in recreational athletes and to discuss their relevance in the differential diagnosis of acute pain syndromes. Methods. A narrative review of the literature was conducted using the PubMed, Scopus, and Google Scholar databases. Publications addressing musculoskeletal injuries in physically active individuals and their clinical presentation as acute pain were analyzed. Results. The analyzed data indicate that injuries involving the lumbar region, abdominal wall, groin, and pelvis represent some of the most frequent causes of acute pain among recreational athletes. The clinical manifestations of these injuries may resemble renal colic, acute abdominal conditions, or inguinal pathologies, which can pose significant diagnostic challenges in clinical practice. Conclusions. The analyzed data indicate that injuries involving the lumbar region, abdominal wall, groin, and pelvic area are among the most common causes of acute pain in recreational athletes. The symptoms of these injuries may clinically resemble renal colic, acute abdominal conditions, or groin pathologies, which may lead to diagnostic difficulties.